2002
DOI: 10.1037/0096-1523.28.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness has a perceptual locus: Evidence from online processing of targets in RSVP streams.

Abstract: Four experiments tested whether repetition blindness (RB; reduced accuracy reporting repetitions of briefly displayed items) is a perceptual or a memory-recall phenomenon. RB was measured in rapid serial visual presentation (RSVP) streams, with the task altered to reduce memory demands. In Experiment 1 only the number of targets (1 vs. 2) was reported, eliminating the need to remember target identities. Experiment 2 segregated repeated and nonrepeated targets into separate blocks to reduce bias against repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
1
29
1
Order By: Relevance
“…In addition, it has been demonstrated that repetition blindness occurs when memory demands are reduced (Chun, 1997;Dux & Marois, 2007;Luo & Caramazza, 1995 and even when no recall is required (Hochhaus & Johnston, 1996;Johnston et al, 2002). Thus, although retrieval failure contributes to some effects of repetition seen in RSVP streams, it is not responsible for all of them.…”
Section: Implications For Theories Of Repetition Blindnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that repetition blindness occurs when memory demands are reduced (Chun, 1997;Dux & Marois, 2007;Luo & Caramazza, 1995 and even when no recall is required (Hochhaus & Johnston, 1996;Johnston et al, 2002). Thus, although retrieval failure contributes to some effects of repetition seen in RSVP streams, it is not responsible for all of them.…”
Section: Implications For Theories Of Repetition Blindnessmentioning
confidence: 99%
“…Research in which this paradigm has been used has identified two fundamental limitations of conscious visual perception: the attentional blink (Broadbent & Broadbent, 1987; Ray k -mond, Shapiro, & Arnell, 1992;Weichselgartner & Sperling, 1987) and repetition blindness (Chun, 1997;Johnston, Hochhaus, & Ruthruff, 2002;Kanwisher, 1987). The attentional blink refers to subjects' impaired ability to report the second of two different targets in an RSVP stream if it appears within 200-600 msec of Target 1 (T1).…”
mentioning
confidence: 99%
“…In fact, as the final draft of this article was being prepared, a published report appeared verifying the prediction that repetition blindness can be obtained with nonwords (Harris & Morris, 2004). Johnston et al (2002) carefully considered the question of whether repetition blindness is more appropriately characterized as a perceptual or as a memory phenomenon. Their evidence for online influences of repetition in a target detection task supported a strong argument against the idea that repetition blindness can be attributed entirely to postlist memory recall processes.…”
Section: Interpreting and Predicting Dissociationsmentioning
confidence: 99%
“…Thus, tokenization of the second presentation of a repeated word fails, and it cannot be reported. In the type-token account of repetition blindness, then, the impaired report of a repeated item is attributed to a failure of encoding or perception that occurs at the moment a repeated word is presented in an RSVP list (see also Hochhaus & Johnston, 1996;Johnston, Hochhaus, & Ruthruff, 2002). …”
mentioning
confidence: 99%
See 1 more Smart Citation